2001
DOI: 10.4319/lo.2001.46.6.1455
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of spectral weighting functions for the solar photobleaching ofchromophoric dissolved organic matter in temperate lakes

Abstract: The effect of solar radiation on the dissolved absorption coefficient (a CDOM []), which reflects the concentration of chromophoric dissolved organic matter (CDOM), was investigated in several lakes near Bariloche, Argentina and in northeastern Pennsylvania, USA. Samples of 0.2 m filtered lake water were exposed in quartz tubes to different portions of the solar spectrum using optical cutoff filters to remove parts of the ultraviolet (UV) region of the solar spectrum. Changes in the spectral absorption in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 42 publications
6
60
0
1
Order By: Relevance
“…This approach, calculation of a spectral weighting function (SWF) using the form of Eq. (10), is similar to prior studies that examined the wavelength dependence of absorption coefficients (Kirk, 1994;Vodacek et al, 1997;Osburn et al, 2001) and photochemical quantum yields for chemical species (Johannessen and Miller, 2001).…”
Section: Wavelength Dependence Of Peroxide Productionsupporting
confidence: 67%
See 2 more Smart Citations
“…This approach, calculation of a spectral weighting function (SWF) using the form of Eq. (10), is similar to prior studies that examined the wavelength dependence of absorption coefficients (Kirk, 1994;Vodacek et al, 1997;Osburn et al, 2001) and photochemical quantum yields for chemical species (Johannessen and Miller, 2001).…”
Section: Wavelength Dependence Of Peroxide Productionsupporting
confidence: 67%
“…The parameter C was an offset value, and was subtracted from the entire absorption spectrum. Photobleaching of CDOM for the photolysis experiments was characterized as the average loss of absorbance (L avg , m À 1 ) over the range of 280 to 500 nm (Osburn et al, 2001).…”
Section: Absorbance Fluorescence and Doc Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This long-pass cutoff filter approach has been used successfully on seawater samples in the determination of AQY spectra for dissolved inorganic carbon (DIC) (Johannessen and Miller 2001) and CO (Ziolkowski 2000). Similarly, Vähälato and Salonen (2000) used the radiation filtering effects of natural lake waters during in situ incubations in place of defined cutoff filters to produce different spectral irradiation for use in calculating AQY spectra for DIC photoproduction, and Osburn et al (2001) used cutoff filters to calculate spectral weighting functions for DOM bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CDOM photobleaching is a function of iron availability and photochemistry (Gao and Zepp 1998;White et al 2003). Osburn and Morris (2003) suggested that CDOM photoreactivity can increase with salinity across an estuarine gradient, but Minor et al (2006) found a decrease in CDOM photobleaching at 280 nm when humic CDOM was added to an artificial salinity gradient used to mimic coastal mixing. Although many studies have investigated factors controlling CDOM photoreactivity, discrepancies in results can arise from different metrics used to define CDOM photoreactivity (Hu et al 2002).…”
mentioning
confidence: 99%